Evaluation of self-esteem in children with attention-deficit/hyperactivity disorder based on event-related potential - Sarraf-Razavi, Mahdiyeh; Rahmanian, Mahdiyeh; Zamani, Maryam; Purabassi, Parivash; Ramezani, Sara; Ghaffari Khaligh, Hadis (Researcher Bulletin of Medical Sciences, 2020)
Background: Self-esteem, the value we place on ourselves, has been associated with effects on health, and life satisfaction. Many studies reported that children with attention-deficit/hyperactivity disorder (ADHD) suffer from low self-esteem has been associated with negative life outcomes. The present study investigated neural correlation of self-esteem in this group compared with typically developing children using the event-related potentials (ERP). Materials and Methods: A total number of 10 children with ADHD were compared with 10 typically developing children matched with their age, gender and IQs. We employed the event-related potential (ERP) technique to explore neural manifestations of implicit self-esteem using the Go/Nogo association task (GNAT). Participants generated a response (Go) or withheld a response (Nogo) to self-words and good or bad attributed. Result: ERP results showed delayed N200 response in frontal areas in bad condition in normal children compared to ADHD children (p <0.05), indicating positive self-esteem. Conclusion: The present study provides neural evidence for probably low self-esteem in ADHD children.